(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the effectiveness of Baitulmaal Muamalat "Sahabat MSME Indonesia" empowerment program on the performance of MSMEs, with intrinsic motivation as a mediating variable. This study used 80 respondents using a quantitative approach and the SmartPLS Structural Equation Modeling (SEM) statistical method. The results showed that training significantly influenced intrinsic motivation and MSME performance. Mentoring significantly influenced MSME performance, not significantly influenced MSME performance mediated by intrinsic motivation. Intrinsic motivation significantly influenced MSME performance. Based on the respondents’ education level, nearly 65% of respondents had a high school or university degree. Therefore, comprehensive training was sufficient for respondents to understand the material presented. Meanwhile, pre-arranged mentoring seemed more focused on meeting schedules, with solutions offered that weren’t necessarily relevant to MSMEs’ problems. Mentoring didn’t significantly influence intrinsic motivation because the material presented didn’t directly impact the intrinsic motivation of entrepreneurs but required more time than the mentoring schedule. The limitations of this study are quantitative methods and the use of a single institution. A combined quantitative and qualitative research model could be used to further enhance the relevance of the results. Further research is needed to test the generalizability of the results and establish causal relationships more comprehensively.